Syphilis Infection During Pregnancy: The Possible Effect on the Course of Pregnancy and Fetal Outcomes—A Case Report and Literature Review - Dovile Kielaite; Saule Januskiene; Virginija Paliulyte (Biomedicines)
Background/Objectives: A wide range of syphilis-related pregnancy complications are encountered in clinical practice. Active surveillance of the epidemiological situation in different countries and a series of retrospective data analyses allow for a comprehensive assessment of the feasible consequences of syphilis infection during pregnancy. The negative effects of infection on reproductive health are also described. Risk-increasing factors (inadequate or late treatment, partner coinfection) and protective factors (timely diagnostics and treatment) are distinguished. The importance of adequate and timely management as well as the accessibility of healthcare and socioeconomic status, which influence health outcomes, are stressed. This article presents a rare case of untreated syphilis infection during pregnancy. The infection was diagnosed during the first antenatal visit; how-ever, treatment was not initiated. At the 33rd week of gestation, the patient was admitted to the hospital because of sparse bloody vaginal discharge. Following sudden fetal hypoxia, an urgent cesarean section was performed at 33 weeks of gestation. A preterm newborn was delivered in critical condition, and congenital syphilis was diagnosed. Methods: We searched the PubMed, Cochrane, and MeSH databases using the key search terms “treponema pallidum”, “sexually transmitted infections”, “pregnancy”, “congenital infection”, “syphilis”, and “congenital syphilis”, as well as their combinations. A total of 28 papers published over a ten-year period were included in the literature review. A clinical case was analyzed. Results: The impact of syphilis on pregnancy is quite evident. Our case showcased one of the most common impacts, i.e., premature birth, of congenital infections with associated bacterial meningitis, respiratory distress syndrome, multiple organ damage, and insufficient weight. Such associations with many adverse pregnancy outcomes as well as congenital syphilis and neonatal defects are often avoidable. Conclusions: Considering the potential consequences of infections, the issue of sexually transmitted diseases remains relevant, and improving diagnostic and treatment opportunities becomes of paramount importance as cases increase.